EDUKASI, PEMBIMBINGAN DAN PELATIHAN PEMBUATAN PAKAN BUATAN PADA PEMBUDIDAYA LOBSTER AIR TAWAR DI DESA PACELLEKANG, KECAMATAN PATALLASANG, GOWA, SULAWESI SELATAN - Jayadi Jayadi; Harlina Harlina; Wahyuti Wahyuti; Beddu Tang; Nursyahran Nursyahran (Jurnal Abdi Insani, 2023)
The Community Partnership Program is Bumdes Bumi Pacellekang Sejahtera (BPS) which is located in Pacellekang Village, Patallasang District, Gowa Regency, South Sulawesi. Bumdes BPS has carried out freshwater lobster cultivation as part of the integrated tourism village program activities. The problem with cultivating freshwater lobsters is that there is a 61% reduction in production due to the high cost of artificial feed. The aim of this service is to increase the knowledge and skills of community groups cultivating freshwater lobsters through education, guidance and training in making artificial feed or pellets. Education and training activities were carried out on Thursday 14 September 2023 at the Assembly Hall, Pacellekang Village. The participants were 15 freshwater lobster cultivators, Bumdes administrators and students who carried out field work practices as MBKM participants. The method used in this activity is a combination of theoretical understanding and the Andragogic learning technique approach method by providing education, guidance and training for the application of appropriate technology for making artificial feed. The material presentation was delivered by the resource person, starting from preparing freshwater lobster feed rations and introducing feed raw materials. Next, guidance and training on making artificial feed is carried out, starting from mixing the feed ingredients and the process of making/molding pellets. The raw materials for feed formulation consist of flour: fish, maggot, bamboo shoots, soybeans, taiopan, fine bran, vitamin mix and CMC with a total protein of 39%. Artificial feed produce used a machine with a production capacity of 100-150 kg/hour. Groups of freshwater lobster farmers can now mix, mix and print artificial feed independently. The Community Partnership Program have independently produced artificial feed for freshwater lobsters.